Geochemical Analysis of Soil and Kalipait River Water as Indicators of Environmental Degradation at the Central Point of the Ijen Geopark Area - Aris Purwowidi Yanto; Cahyaning Putri Binarwanti, Arief Setya Wijaya, Aditya Bachtiar Yuniardi, Karuna Ikbar Arsy, Noni Di (Integrative Perspectives of Social and Science Journal, 2026)
Ijen Geopark is well known for its distinctive volcanic landscapes, particularly Mount Ijen and the Ijen Crater Lake, which is recognized as having one of the highest levels of acidity in the world. The Kalipait Acid Stream Geosite is one of the geological sites within Ijen Geopark, located in Kalianyar Village, Ijen District, Bondowoso Regency. This geosite consists of a sulfur-rich river flow with a high H₂SO₄ concentration, resulting in extremely low water pH. A qualitative descriptive approach was employed to analyze environmental degradation in the middle section of the Kalipait River. The pH measurements indicate that the sampling locations range from 2.3 to 2.4, confirming that the Kalipait River is highly acidic. Furthermore, geochemical analysis of the soil reveals that the soils in the study area tend to have low base nutrient contents, particularly calcium (Ca) and magnesium (Mg), across all analyzed samples. Total calcium content ranges from 0.044% to 0.094%, while total magnesium content ranges from 0.0072% to 0.0093%. These findings demonstrate that geochemical parameters of soil and Kalipait River water are effective as early indicators of environmental degradation. Therefore, integrated management efforts, regular monitoring, and control of activities within the Ijen Geopark area are necessary to maintain ecological sustainability and conservation value.